Fertilizer types on corn yields (zea mays l.) in Kampar, Perak - Wong, Eu Jeff (2025)
The global population is increasing, and optimizing food production has become a crucial way to address this challenge. Sweet corn (Zea mays L.) is a staple crop because it is both nutritious and affordable. However, in Malaysia, sweet corn production has not been self-sufficiency due to a paucity of knowledge in fertilizer management. This study investigated the effects of NPK 12:12:17, calcium boron (Ca/B), and biostimulant on the yield and anthesis timing of different sweet corn varieties commonly grown in Kampar, Perak, Malaysia. A split-plot design was done in UTAR Agriculture Park B, with two varieties, which were King Corn F1 316 and Sweetcorn King Raja SC 9001, and five different treatments: control (no fertilizer), NPK 12:12:17, NPK 12:12:17 + Ca/B, NPK 12:12:17 + biostimulant, and NPK 12:12:17 + Ca/B + biostimulant. The corn variety of F1 316 performed statistically significantly better than SC 9001 for cob’s fresh weight (g), cob length (cm), cob girth (cm), and the number of kernels per column. Both varieties showed statistically insignificant in 100-kernel weight (g). For fertilizer treatment, NPK 12:12:17 was statistically significant than control in producing a heavier 100-kernels weight (g). Moreover, a significant interaction effect was observed between variety and fertilizer type for 100-kernel weight (g), with the combination of variety F1 316 and NPK 12:12:17 yielding the heaviest kernels (g). These highlights the importance of distinguishing between apparent yield (whole cob) and actual yield (only kernels), suggesting that farmers should prioritize the corn varieties and types of fertilizer that may lead to a higher actual yield. NPK 12:12:17 can improve corn yield, while Ca/B supplementation is essential when deficiency is detected, and glycine-based biostimulants are beneficial when plants experience drought stress. Future studies should investigate how different fertilizer types affect the quality traits (i.e., shelf-life, physicochemical properties and nutrient content) of sweet corn.